Effect of programmed physical activity on the physical fitness of adolescent students - Edson Dos Santos Farias; Wellington Roberto Gomes Carvalho; Ezequiel Moreira Gonçalves; Gil Guerra Guerra-Júnior (Universidade Federal de Santa Catarina, 2010)
The objective of this study was to determine the influence of programmed physical activity on the physical fitness of adolescent students over one school year. The sample consisted of 383 students (age range: 10 to 14 years) divided into two groups: 186 cases (96 boys and 90 girls) and 197 controls (108 boys and 89 girls). An intervention study with pre- and post-tests was conducted, in which the intervention group was submitted to programmed physical activity, while the control group underwent conventional classes of school physical education. Physical fitness was assessed by sit-and-reach (flexibility), muscle endurance (elbow flexion and extension) and aerobic endurance (run/walk, 9 min) tests. Motor performance observed in the three tests (flexibility, strength and endurance) did not improve from pre-test to post-test in either group, but comparison of the intervention and control groups showed significant improvement in the strength and endurance tests for both genders in the intervention group. Boys of the two groups also showed dominance in the strength and endurance tests. In general, higher muscle strength and cardiorespiratory fitness and lower flexibility were observed for boys when compared to girls, and all parameters increased in the post-test and were higher in the intervention group compared to control A significant difference in flexibility was only observed between genders. With respect to muscle strength, a significant difference was observed between genders and between the intervention and control group after adjustment for age and socioeconomic level. Cardiorespiratory fitness differed significantly between genders and between the intervention and control group.